2019
DOI: 10.1002/cam4.2540
|View full text |Cite
|
Sign up to set email alerts
|

DOK6 promoter methylation serves as a potential biomarker affecting prognosis in de novo acute myeloid leukemia

Abstract: BackgroundDownstream of tyrosine kinase 6 (DOK6), which is specifically expressed in the nervous system, was previously recognized as an adapter only in neurite outgrowth. Recent studies also demonstrated the potential role of DOK6 in solid tumors such as gastric cancer and breast cancer. However, previous studies of DOK6 have not dealt with its roles in myeloid malignancies. Herein, we verified the promoter methylation status of DOK6 and further explored its clinical implication in de novo acute myeloid leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Deneberg et al reported that a high level of global methylation predicted a poorer complete remission rate and that p15 methylation was associated with better OS and disease-free survival (DFS) (35). Sun GK et al reported that methylation of the DOK6 promoter predicts longer survival (36). These studies suggested that the methylation level of genes can be valuable prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Deneberg et al reported that a high level of global methylation predicted a poorer complete remission rate and that p15 methylation was associated with better OS and disease-free survival (DFS) (35). Sun GK et al reported that methylation of the DOK6 promoter predicts longer survival (36). These studies suggested that the methylation level of genes can be valuable prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA isolation was conducted as reported previously. 24 Reverse transcription reaction with 40 μl volume was composed of 5× buffer 10 mM, 10 mM of dNTPs (deoxyribonucleoside triphosphates), 10 μM of random hexamers, 80 U of RNAsin, and 200 U of MMLV reverse transcriptase (Eppendorf). The reaction conditions were incubated for 10 min at 25℃, 60 min at 42℃, and then stored at −20℃.…”
Section: Rna Isolation Reverse Transcription and Rt-qpcrmentioning
confidence: 99%
“…Total RNA was extracted from BMNC using Trizol reagent (Invitrogen Life Technologies, USA) as described previously [13][14][15][16][17]. 2 ug of total RNA were reverse transcribed into cDNA using 10 umol/l random primers, 200 U MMLV reverse transcriptase, 0.5 mmol/l dNTP, 10 mmol/l dithiothreitol, and 25 U RNase inhibitors.…”
Section: Rna Isolation and Reverse Transcriptionmentioning
confidence: 99%
“…The primers for ITGB2 expression were 5′-GATGACGGCTTCCATTTCGC -3′ (forward) and 5′-TGGGGATGATCTCGGTGAGT -3′ (reverse). Reaction conditions and PCR cycling were conducted as previously described [13][14][15][16][17] except for the optimized primer annealing temperatures (60 °C). The relative quanti cation was calculated using the ΔΔCT method and normalized to the ABL1 housekeeping gene.…”
Section: Rt-qpcrmentioning
confidence: 99%
See 1 more Smart Citation